2019
DOI: 10.1155/2019/7943636
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results and MRI Evaluation of Patellar Osteochondral Fracture Fixation following Patellar Dislocation

Abstract: Aim. The aim of the study was to analyze the clinical results and MRI scans after transpatellar osteochondral fracture fixation following patellar dislocation. Methods. Our study group comprised 17 patients with patellar dislocation followed by osteochondral fracture of the articular surface of the patella. All patients underwent surgery where the fractured osteochondral fragments of the patella were attached using the transpatellar suture technique. The mean age at the time of surgery was 14.1 years, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Although it was not because of the abnormality depicted on the SL view that prompted the MR scan, it has relevance in the evaluation of the patella and patellofemoral joint 5,9,11,12 as shown in this case study. There is a paucity of literature about the use of SL view in the evaluation of acute patellofemoral joint injuries.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although it was not because of the abnormality depicted on the SL view that prompted the MR scan, it has relevance in the evaluation of the patella and patellofemoral joint 5,9,11,12 as shown in this case study. There is a paucity of literature about the use of SL view in the evaluation of acute patellofemoral joint injuries.…”
Section: Discussionmentioning
confidence: 83%
“…Intraarticular haematoma of the knee joint is produced from many injuries including patellar dislocation which oftentimes results in osteochondral fractures in which case a SL view should be included in the trauma radiographic series. 11 In the UK for instance, SL view is not routinely performed as part of the radiographic series in acute knee injuries. Nevertheless, the standard SL view requires a good amount of flexion 6 at the knee and therefore presents as a problem in the injured.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have similarly shown that suture fixation restores the surface of articular cartilage but that there may be thinning or narrowing of the cartilage layer on long-term follow-up with their technique that involved suture fixation through the fracture fragment. 17 Histologic investigation of subchondral bone and articular cartilage quality would more precisely characterize healing after treatment of osteochondral fractures with this fragment-sparing technique. Have 3-4 strands of Vicryl suture between each knotless anchor.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a study that analyzed 134 OCFs that were associated with patellofemoral dislocation; Uimonen et al found that 63% of the fractures occurred in the patella, 34% occurred in the lateral femoral condyle, and 3% occurred in both locations 10 . In our analysis of 6 studies that included 171 patients with an OCF after acute patellofemoral instability, we found that 132 (77.2%) sustained a patellar fracture and 39 (22.8%) sustained a femoral fracture (see Appendix) [11][12][13][14][15][16] .…”
Section: Epidemiologymentioning
confidence: 99%